Adjuvant Chemotherapy Is Not Guided by Pathologic Treatment Effect After Neoadjuvant Chemotherapy in Pancreatic Cancer. Issue 8 (September 2021) - Gleeson, Elizabeth M.; Leigh, Natasha; Golas, Benjamin J.; Magge, Deepa; Sarpel, Umut; Hiotis, Spiros P.; Labow, Daniel M.; Pintova, Sofya; Cohen, Noah A.
Abstract : Objectives: Currently, there is no guidance for optimal adjuvant chemotherapy selection after pancreatectomy with a partial or poor response to neoadjuvant therapy. This study seeks to describe an institution's practice patterns of adjuvant chemotherapy selection after neoadjuvant therapy. Methods: Patients at a single institution receiving neoadjuvant chemotherapy followed by pancreatectomy for pancreatic cancer were reviewed. Patients enrolled in trials or without follow-up were excluded. Types of chemotherapy, the College of American Pathologists pathologic tumor response, and medical oncology plans were recorded. Results: Forty-one patients met inclusion criteria. Pathologic review of treatment effect demonstrated that 3 patients (7.3%) had complete pathologic response, 3 (7.3%) had near complete pathologic response, 16 (39%) had partial response, and 14 (34.1%) had poor/no response to neoadjuvant chemotherapy. Fourteen of the 30 patients with partial or poor response (46.7%) received an alternate adjuvant regimen. Pathologic response to neoadjuvant chemotherapy specifically guided therapy in 11 (30.5%) patients. Conclusions: Despite 73.1% of patients with partial or poor response to neoadjuvant chemotherapy, only 46.7% received a different adjuvant regimen. Medical oncologists infrequently considered treatment effect when choosing adjuvant therapy. Pathologic response to neoadjuvant chemotherapy should be considered when selecting adjuvant chemotherapy.